The rise of the photosynthetic rate when light intensity increases is delayed in ndh gene-defective tobacco at high but not at low CO2 concentrations - Martín, Mercedes; Noarbe, Dolores M.; Serrot, Patricia H.; Sabater, Bartolomé (Frontiers in Plant Science, 2015)
The 11 plastid ndh genes have hovered frequently on the edge of dispensability, being absent in the plastid DNA of many algae and certain higher plants. We have compared the photosynthetic activity of tobacco (Nicotiana tabacum, cv. Petit Havana) with five transgenic lines (ndhF, pr-ndhF, T181D, T181A and ndhF FC) and found that photosynthetic performance is impaired in transgenic ndhF-defective tobacco plants at rapidly fluctuating light intensities and higher than ambient CO2 concentrations. In contrast to wild type and ndhF FC, which reach the maximum photosynthetic rate in less than one min when light intensity suddenly increases, ndh defective plants (ndhF and T181A) show up to a 5 min delay in reaching the maximum photosynthetic rate at CO2 concentrations higher than the ambient 360 ppm. Net photosynthesis was determined at different CO2 concentrations when sequences of 130, 870, 61, 870 and 130 μmol m−2 s−1 PAR sudden light changes were applied to leaves and photosynthetic efficiency and entropy production were determined as indicators of photosynthesis performance. The two ndh-defective plants, ndhF and T181A, had lower photosynthetic efficiency and higher entropy production than wt, ndhF FC and T181D tobacco plants, containing full functional ndh genes, at CO2 concentrations above 400 ppm. We propose that the Ndh complex improves cyclic electron transport by adjusting the redox level of transporters during the low light intensity stage. In ndhF-defective strains, the supply of electrons through the Ndh complex fails, transporters remain over-oxidized (specially at high CO2 concentrations) and the rate of cyclic electron transport is low, impairing the ATP level required to rapidly reach high CO2 fixation rates in the following high light phase. Hence, ndh genes could be dispensable at low but not at high atmospheric concentrations of CO2.